Seroprevalence of Toxoplasma gondii in females alpacas of SAIS Pachacutec, Central Sierra of Peru - De La Cruz C., Hernán (2011)
The objective of this study was to determine the seroprevalence of antibodies against Toxoplasma gondii in alpacas at the production unit of Cuyo, part of SAIS Pachacutec in the Central Sierra of Peru. Blood samples were collected in 258 female alpacas in January 2003. Sera were tested against T. gondii antibodies by the Indirect Immunoflorescence test (IFI). The results showed that 8.5 ± 3.4% (22/258) of animals had antibodies against the parasite. This frequency is lower than in other alpaca breeding regions of the country.